2010
DOI: 10.1177/0022167810361687
|View full text |Cite
|
Sign up to set email alerts
|

A State of Readiness: An Exploration of the Client’s Role in Meeting at Relational Depth

Abstract: This version is available at https://strathprints.strath.ac.uk/26817/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…Dialogic formulations of empathy (Schmid, 2006) would be representative of this and include the client's empathic awareness of the therapist's empathic awareness of the client's initial experience. This process is similar to the notion of mutual empathy proposed within the feminist relational psychotherapy (Jordan, 2000) and of the mutual understanding described in experiences of relational depth (Knox & Cooper, 2011;Mearns & Cooper, 2005).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Dialogic formulations of empathy (Schmid, 2006) would be representative of this and include the client's empathic awareness of the therapist's empathic awareness of the client's initial experience. This process is similar to the notion of mutual empathy proposed within the feminist relational psychotherapy (Jordan, 2000) and of the mutual understanding described in experiences of relational depth (Knox & Cooper, 2011;Mearns & Cooper, 2005).…”
Section: Introductionsupporting
confidence: 69%
“…Relational depth has been evidenced in recent studies that concluded both clients (Knox, 2008;Knox & Cooper, 2011;MacMillan & McLeod, 2006) and therapists (Cooper, 2005;Knox & Cooper, 2010;Mearns & Cooper, 2005) reported experiences of moments of relational depth. There is also now a newly developed measure for capturing experiences of relational depth within therapeutic encounters (Wiggins, Elliott, & Cooper, 2012).…”
Section: Dialogic and Mutual Aspects In Person-centered Therapymentioning
confidence: 95%
“…Neither do we mean to imply that therapists are unimportant. In concert with the observation by Knox and Cooper (2011) that moments of relational depth reflected clients' readiness and initiative as well as those of the therapists, our participants' testimony suggests that a realistic clinical understanding of the process and outcome of therapy requires considering both clients' and therapists' plans, intentions, and will. These studies demonstrate that there is scope for continuing research in the area of client agency.…”
Section: Limitations and Conclusionmentioning
confidence: 59%
“…These factors include counselor presence (Mearns, , ; Mearns & Cooper, ); transparency and immediacy (Cooper, 2013b; Mearns & Cooper, ; Mearns & Schmid, ); self‐awareness (Cooper, 2013b; Mearns & Cooper, ); care for the client (Cooper, 2013b); fearlessness (Mearns, , ); ability to create a safe environment, ability to forgo preconceived notions of clients or the desire to fix clients, ability to let go of specific techniques, and ability to listen deeply (Mearns & Cooper, ); acceptance of the client (Cooper, 2013b; Mearns & Schmid, ); willingness to be affected by the client and invite this deeper encounter (Mearns & Cooper, ; Mearns & Schmid, ); and commitment to the client, openness to the experience, existential‐level communication, emphasis on the relationship, willingness to have an impact the client, and awareness of the environment and the power differential (Mearns & Schmid, ). Qualitative studies of therapists' (Cooper, ; Macleod, ) and clients' (Knox, , ; Knox & Cooper, , ; McMillan & McLeod, ) experiences of relational depth also shed some light on this question. However, there remains a dearth of empirical research exploring the specific counselor factors that contribute to the ability to invite and facilitate these moments of relational depth.…”
mentioning
confidence: 99%